Mechanical behavior and factors influencing axial splitting energy absorbers and optimized application for rock bolts. (August 2020) - Dai, Lianpeng; Xiao, Yonghui; Pan, Yishan; Wang, Aiwen; Fan, Congcong; Guo, Jianlin
Abstract: An axial splitting energy absorber for rock bolts was designed to adapt to the large deformation of surrounding rocks in deep roadways. This paper presents an experimental investigation of the mechanical behavior of the splitting energy absorbers with different parameters. The effects of materials, diameter-to-thickness ratio, prefabricated cuts, induced splitting dies, anti-curling splitting conditions, and oblique loading on the performance of the components were studied. The test results indicated that the splitting process of the component made of Q235 steel with four prefabricated cuts, is more stable; the smaller the diameter-to-thickness ratio, the higher the constant axial load level of the component; the anti-curling condition can only increase the load level of the components by 6%; the components have the advantages of "strong deformation sensitivity and weak load sensitivity" when subjected to oblique loading. Eventually, the parameters of the energy absorber were optimized for the rock bolts, i.e., the components have an inner diameter of 26 mm, a wall thickness of 4 mm, and four prefabricated cuts with a free-curling splitting mode. The novel anchor bolts exhibited stable energy absorption behaviors when subjected to static and dynamic loading. Moreover, the energy absorbers increased the stability, thereby yielding a rebar stroke of 40–200 mm. More importantly, serial research work on energy-absorbing components with various parameters will establish the experimental foundation for the application of components in various mining environments.